In vivo brain changes in late-life depression - Sexton, C (2011)
Late-life depression (LLD) is common illness, frequently associated with neuropsychological impairment. Disruption of frontal-subcortical and limbic networks may play a key role in LLD and can be examined using magnetic resonance imaging (MRI). Grey matter (GM) can be examined using T1-weighted MRI, white matter (WM) using diffusion tensor imaging (DTI), and functional connectivity using resting-state functional MRI (fMRI). To clarify the roles of GM, WM and functional connectivity in LLD, systematic reviews and meta-analyses of T1-weighted MRI, DTI and resting-state fMRI studies of depression were performed. The literature provided evidence for GM and WM abnormalities within frontal-subcortical and limbic networks, and increased functional connectivity within the default-mode network, in depression. To examine whether results gained from different techniques are complementary, multi-modal MRI was used to compare GM, WM and functional connectivity between thirty-six participants with LLD and twenty-five control participants. WM integrity was widely reduced in LLD, without significant group differences in GM or functional connectivity. To investigate whether neuropsychological deficits represent independent processes with specific neural correlates, or whether they can be explained by a core deficit, the relationships between neuropsychological and MRI measures were explored. Executive function and processing speed were found to represent core deficits that contribute to impairment in other domains; and impaired performance was correlated with reduced frontal WM integrity. Episodic memory deficits were dependent on executive function and processing speed; and associated with reduced frontal and hippocampal WM integrity. The relationships between age at onset, severity and MRI measures of GM, WM and functional connectivity were also investigated. Later onset was associated with reduced WM integrity, in line with the vascular hypothesis. Earlier onset was associated with greater duration of illness and reduced hippocampal volume, consistent with the glucocorticoid cascade hypothesis. Severity was not associated with any MRI measure. This thesis strongly supports the hypothesis that WM abnormalities in frontal-subcortical and limbic networks play a key role in LLD, with abnormalities related to neuropsychological impairment and compatible with the vascular hypothesis.